An Improvement of Livestock Feed Quality Through the Production of Fermented Complete Feed in the Karya Manunggal Livestock Group, Donokerto, Turi, Sleman, Yogyakarta - Anam, Moh Sofi'ul; Baskara, Aji Praba; Agus, Ali; Setyawan, Erif Maha Nugraha; Akhda, Najmu Tsaqib (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
This community service aimed to assist farmers in improving their knowledge and quality of feed by producing fermented complete feed (FCF). The community service occurred from June to November 2019 in the Karya Manunggal livestock group in Donokerto, Turi, Sleman. The activities included observing the initial conditions of the group, providing counseling, conducting FCF production training, evaluating the products, and utilizing the trained products for the livestock. The results of the activities indicated an increase in farmers' knowledge about manufacturing concentrate and feed supplements, feed preservation technology, and FCF, each by 80%, 73%, and 95%, respectively. Farmers successfully produced FCF with good quality, as indicated by the acidic pH of 4.31. The palatability of FCF was also excellent for livestock. The average daily gain in sheep with FCF supplementation was 0.156 grams/head/day, while the farmers' feed supplementation was 0.113 grams/head/day. The community service activities in the Karya Manunggal livestock group conclude the improvement of farmers' knowledge and skills in terms of livestock nutritional needs, balanced feed formulation, and the utilization of fermentation technology in feed production. The success of these activities is also evident in the increased effectiveness of feed and cost efficiency following the implementation of FCF.